Participative and Practical Goal-setting in Enterprise Systems Learning. Issue 5 (3rd September 2022) - Li, Yaojie; Ho, Johnny; Hodhod, Rania; Pitts, Jennifer; Finley, John
ABSTRACT: This research examines how dynamic course goal-setting can affect students' enterprise systems learning and career choice, through a university alliance program. It also explores the learners' cognitive and affective responses in this industry-academia collaboration. Applying the grounded theory method, we interpret the action-interaction among instructors, learners, and the enterprise software vendor while proposing a model of participative and practical goal-setting. Lastly, we discuss contributions to goal-setting theory and enterprise systems education and practical implications for similar course design and development.